SIKAP KRITIS TERHADAP KUALITAS PENDIDIKAN AGAMA HINDU DI TENGAH KONDISI UMAT YANG MENCEMASKAN - Putu Dana Yasa; Febri Vive Kananda (Veda Jyotih: Jurnal Agama dan Sains, 2022)
The quality of Hindu religious education that has existed since ancient times and has developed until now, of course, must receive greater attention. This is important as an effort to address various religious issues. In the midst of the condition of Hindus who are currently in an anxious position due to a lack of basic understanding of their religious teachings, of course it is a shared responsibility, especially the responsibility of Hindu intellectuals who play an important role in conveying religious teachings contained in the sacred Vedic literature. Various types of improvements are needed in the Hindu education system so that the objectives of the Hindu education system can be achieved. Another thing that is also needed is mutual awareness to maintain Hinduism so that it is able to have better quality and can have a strong belief in the teachings they have.